Unraveling the microbiome of a thermophilic biogas plant by metagenome and metatranscriptome analysis complemented by characterization of bacterial and archaeal isolates. Issue 1 (December 2016) - Maus, Irena; Koeck, Daniela; Cibis, Katharina; Hahnke, Sarah; Kim, Yong; Langer, Thomas; Kreubel, Jana; Erhard, Marcel; Bremges, Andreas; Off, Sandra; Stolze, Yvonne; Jaenicke, Sebastian; et al.
Abstract Background One of the most promising technologies to sustainably produce energy and to mitigate greenhouse gas emissions from combustion of fossil energy carriers is the anaerobic digestion and biomethanation of organic raw material and waste towards biogas by highly diverse microbial consortia. In this context, the microbial systems ecology of thermophilic industrial-scale biogas plants is poorly understood. Results The microbial community structure of an exemplary thermophilic biogas plant was analyzed by a comprehensive approach comprising the analysis of the microbial metagenome and metatranscriptome complemented by the cultivation of hydrolytic and acido-/acetogenicBacteria as well as methanogenicArchaea . Analysis of metagenome-derived 16S rRNA gene sequences revealed that the bacterial generaDefluviitoga (5.5 %), Halocella (3.5 %), Clostridium sensu stricto (1.9 %), Clostridium cluster III (1.5 %), andTepidimicrobium (0.7 %) were most abundant. Among theArchaea, Methanoculleus (2.8 %) andMethanothermobacter (0.8 %) were predominant. As revealed by a metatranscriptomic 16S rRNA analysis, Defluviitoga (9.2 %), Clostridium cluster III (4.8 %), andTepidanaerobacter (1.1 %) as well asMethanoculleus (5.7 %) mainly contributed to these sequence tags indicating their metabolic activity, whereasHallocella (1.8 %), Tepidimicrobium (0.5 %), andMethanothermobacter (<0.1 %) were transcriptionally less active. By applying 11 different cultivation strategies, 52 taxonomically different microbial isolates representing the classesClostridia, Bacilli, Thermotogae, Methanomicrobia andMethanobacteria were obtained. Genome analyses of isolates support the finding that, besidesClostridium thermocellum andClostridium stercorarium, Defluviitoga tunisiensis participated in the hydrolysis of hemicellulose producing ethanol, acetate, and H2 /CO2 . The latter three metabolites are substrates for hydrogentrophic and acetoclastic archaeal methanogenesis. Conclusions Obtained results showed that high abundance of microorganisms as deduced from metagenome analysis does not necessarily indicate high transcriptional or metabolic activity, and vice versa. Additionally, it appeared that the microbiome of the investigated thermophilic biogas plant comprised a huge number of up to now unknown and insufficiently characterized species.